KEBIJAKAN IMPOR BERAS DI INDONESIA 1930-1966 - , TAUFIK AL ZURJANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Economic depression affected the food crisis in the people and began to intervention Dutch Colonial Government in food import policy. Previously, Dutch Colonial is giving more space process of determining the market price. The period 1930 until 1966 was important period to see how crucial influence on Indonesia rice import policy. First, the mechanism price of rice by the Dutch Colonial Government. Second, the inability of Japanese Colonial Government to import rice when rice production at the local level is less. Third, the revolution and the political instability in the early independence come about the effectiveness of the policy of the Government of the Republic. The danger of famine, malnutrition, and endemic of diseases to give the impression that the policy is carried out at the point and very biased colonial. This study is using a history method as the background, in: topic selection, source collection, verification, interpretation, and writing. Keywords: import policies, rice import, food crises